Wet deposition of fossil and non-fossil derived particulate carbon: insights from radiocarbon measurement - Zhang, Yan-Lin
Radiocarbon (14C) measurements of both organic carbon (OC) and elemental carbon (EC) allow a more detailed source apportionment, leading to a full and unambiguous distinction and quantification of the contributions from non-fossil and fossil sources. A thermal-optical method with a commercial OC/EC analyzer to isolate water-insoluble OC (WIOC) and EC for their subsequent 14C measurement was applied for the first time to filtered precipitation samples collected at a costal site in Portugal and at a continental site in Switzerland. Our results show that WIOC in precipitation is dominated by non-fossil sources such as biogenic and biomass-burning emissions regardless of rain origins and seasons, whereas EC sources are shared by fossil-fuel combustion and biomass burning. In addition, monthly variation of WIOC in Switzerland was characterized by higher abundance in warm than in cold seasons, highlighting the importance of biogenic emissions to particulate carbon in rainwater. Samples with high particulate carbon concentrations in Portugal were found to be associated with increased biogenic input. Despite the importance of non-fossil sources, fossil emissions account for approximately 20% of particulate carbon in wet deposition for our study, which is in line with fossil contribution in bulk rainwater dissolved organic carbon as well as aerosol WIOC and EC estimated by the 14C approach from other studies.